The potential of Islamic financial institutions in promoting small and medium enterprises (SMEs) in Ethiopia - ALI, Abdu Seid; BUSHERA, Ibrahim; YESUF, Abdurahman Jemal (Journal of Economics and Political Economy, 2020)
Abstract. It is universally proclaimed that SMEs are engines of growth and development in various countries in the world. Nonetheless, access to finance remained an acute obstacle. This paper aims to assess the potential of Islamic financial institutions in promoting SMEs to get access to alternative financial services in Ethiopia. Similar to other developingcountries, SMEs in Ethiopia have lack of access to finance and alternative financial services. Hence, the experience of other countries show that Islamic financial institutions have been providing alternative services based on risk sharing, asset-based and ethical principlesin order to achieve financial inclusion and wide-ranging growth. In order to encourage SMEs to get access to alternative source of finance, regulatory and legal frameworks, proper financial infrastructure, market and industry issues, awareness creation, and producing trained workforce should get proper attention. Keywords. SMEs, Islamic financial institutions, Access to finance, Ethiopia. JEL. G21, G51, D25.